Intestinal obstruction from calcium polystyrene sulfonate in pediatric cancer patients - Songpon Getsuwan; Patcharee Komwilaisak; Napat Laoaroon; Patchareeporn Tanming; Kunanya Suwannaying; Surapon Wiangnon; Arunee Jetsrisuparb (Elsevier, 2022)
Tumor lysis syndrome (TLS) is common in some childhood hematologic malignancies. Calcium polystyrene sulfonate (CPS) is occasionally prescribed for hyperkalemia in TLS. We reported two children with intestinal obstruction, a serious adverse effect from high-dose CPS. Both cases were constipated prior to chemotherapy with vincristine. While one patient recovered from the obstruction by surgery, the other was successfully managed by manual evacuation. After the obstruction, both children experienced recurrent constipation, which was aggravated by vincristine. Using CPS in children with preexisting constipation or ileus could lead to adverse outcomes. We would like to propose that effective treatment for fecal disimpaction is necessary when starting CPS with vincristine in children with constipation.